Memoirs of the Life, Religious Experience, Ministerial Travels, and Labours of Mrs. Elaw - Elaw, Zilpha, approximately 1790-1846 (Book collections on Project MUSE., 2021)
"The memoirs of Zilpha Elaw, an antebellum Black woman, document the first twenty years of her forty-year itinerant ministry as a Methodist preacher in the United States and England in the 1800s. With an introduction, annotations, and timeline by Kimberly D. Blockett"--